Ajaran Pokok, Sekte-Sekte dan Ajaran Masing-Masing (Al-Murji’ah, Al-Mu’tazilah, Al-Khawarij, Al-Farabi, Al-Qadariyah dan Al-Jabariyah) - Harsono Harsono; M. Fatahurahman; Khairul Amri; Samsul Fajri; Juwairiani Juwairiani (Departement of Mathematics Education, 2023)
In the history of Islamic civilization, several groups emerged which cannot be denied that basically started from wanting to address the political problems that existed among Muslims at that time. Islam really values reason and even makes it a differentiator between humans and other creatures so that it is responsible as a caliph on earth, so that more than one theology school was born. This study aims to analyze the main teachings, sects, and teachings of each stream from the Al-Murji'ah, Al-Mu'tazilah, Al-Khawarij, Al-Farabi, Al-Qadariyah and Al-Jabariyah sects. This study uses the documentation method which is used as a data source in the form of sources from pictures or videos, works, and written things that can provide information. The results obtained show that of the six schools analyzed have their own views, teachings, sects, and beliefs. However, the most important thing is that there is no need to argue about it and only need to respect each other.